Antoni, król Polski. Epizod z dziejów angielskiej satyry politycznej w ujęciu literaturoznawstwa i nauk społecznych - Żurek, Agnieszka (2024)
This paper investigates the nickname of “king of Poland” given to Anthony Ashley Cooper, 1st Earl of Shaftesbury (1621–1683), in pamphlets produced by his Tory adversaries. The research subject is primarily the source of the nickname, its role in the propaganda war between Tories and Whigs and its consequences for the image of Poland in English discourse. An interdisciplinary research perspective combines literary studies (especially close reading supplemented by tools developed by new historicism), history, social and political studies. The research material covers 32 verse and prose pamphlets printed between 1681–1684 which attribute the nickname “king of Poland” to Shaftesbury. The conclusion is that although the pamphleteers did not show interest in actual intricacies of Polish politics, their works demonstrate stereotypes about social and religious issues of Poland and, reversely, they influence the English opinions about Poland.
Keywords: Restoration satire; English political satire; Restoration pamphlets; Exclusion Crisis; John III Sobieski; Anthony Ashley Cooper (1621–1683)